Elucidating the associations of polymorphism of growth hormone gene with milk production traits in Jamunapari goats of India - Mandal, Ajoy; Prajapati, B. K; Singh, K. P; Rout, P. K.; Roy, R. (Indian Journal of Dairy Science, 2024)
Growth hormone (GH) gene can be utilized as a major gene because its polymorphisms have been associated to milk traits in various livestock species. The aim of this present study was to investigate single-strand conformation polymorphism (SSCP) in the exon 1, 3 and 5 of gGH (goat GH) gene and to evaluate the possible associations with milk traits in Jamunapari goat, maintained at the ICAR- Central Institute for Research on Goats, Makhdoom, Uttar Pradesh, India. In this study, 100 primiparous lactating goats were randomly chosen, and their productive performances like 90-days, 140-days and total milk yield as well as milk compositional traits like fat %, SNF%, casein%, protein%, lactose% and ash % of three consecutive lactations were recorded. The exon 1, 3 and 5 of the gGH gene was PCR amplified and the resulting products were analyzed by SSCP. Two conformational patterns (A and B) for each the GH exon 3 and 5 were detected but no polymorphism existed in exon 1 of growth hormone gene.The frequency of the patterns varied from 41.4 to 58.6% in these two fragments. Association studies of SSCPs patterns at GH gene with milk production and milk composition traits in Jamunapari breed showed that only polymorphic patterns at exon 3 were positively associated with milk production traits, i.e., with 90-days milk yield, 140-days milk yield and total milk yield of animals but there was no significant effect on milk composition traits. Animals with pattern A/A for exon 3 were significantly superior milk producers (P<0.01) than animals having B/B pattern for 90-days, 140-days and total milk yield of animals, whereas GH conformation patterns (A and B) for exon 3 didn’t have any impact on milk compositions. Further, in case of exon 5, the milk yields and milk compositions of animals didn’t vary significantly between animals having different GH conformation patterns (A and B). These findings may be used for preserving genetic diversity of the population and may be useful for marker assisted selection in order to improve dairy production for this breed.